Detection and isolation of Listeria spp. and Listeria monocytogenes in ready-to-eat foods with various selective culture media - Jamali, H.; Chai, L.C.; Thong, Kwai Lin (Elsevier, 2013)
The objectives of this study were to determine the prevalence of Listeria spp., specifically Listeria monocytogenes in ready-to-eat (RTE) foods and ascertain the efficiency of detecting L. monocytogenes with different selective culture media. A total of 396 RTE food samples were purchased from hypermarkets and streetside hawker stalls to examine the presence of Listeria spp. and L. monocytogenes. The presumptive isolates were characterized biochemically and were further confirmed by Polymerase Chain Reaction (PCR). Out of 396 samples, Listeria spp. was detected in 71 (17.9%) samples in which 45 (11.4%) were positive for L. monocytogenes. Among the studied RTE foods, salads and vegetables had the highest prevalence (14.7%) of L. monocytogenes, followed by chicken and chicken products (13.2%), beverages (10%), eggs and egg products (9.5%), beef and beef products (6.7%), lunch boxes (6.7%) and seafood and seafood products (6.7%). Both Listeria selective agar and PALCAM agar displayed a low sensitivity and specificity in L. monocytogenes detection compared to CHROMagar™ Listeria which demonstrated 96.9% of sensitivity and 99.1% of specificity in L. monocytogenes detection in naturally-contaminated foods. In conclusion, this work revealed consumption of RTE foods as a potential risk of listeriosis in this region. The high contamination rate of L. monocytogenes in salads and vegetables from hypermarkets and streetside hawker stalls was of great concern due to emerging fresh produce-borne L. monocytogenes globally. The scenario warrants further surveillance and action by the local authority to control the incidence of L. monocytogenes contamination in RTE foods.